Challenges along the Middle Corridor: A Case Study for Port of Baku - Yaqoobi, Obaidullah; Abdul Halim, Hasinah; Rahimov, Murad (ADA University, 2024)
The Middle Corridor is a modern version of the Ancient Silk Road that connects China, the Central Asian countries of Uzbekistan, Kazakhstan, and Turkmenistan with Azerbaijan and Georgia in the South Caucasus, and eventually into Türkiye. It faces geopolitical and non-geopolitical challenges that serve to influence its vital importance in relation to the INSTC or the North-South Corridor and the Northern Corridor. The project investigates these challenges and provides policy measures that look at political advocacy by navigating the intricacies of intercultural communication between Iran and Russia, improvement of the digitalised port model of the Port of Baku, and technological advocacy by way of knowledge and data sharing, as well as the creation of a 4IR-ready workforce.
Keywords: Azerbaijan -- Foreign relations; Port management -- Azerbaijan -- Baku; Technology -- Economic aspects -- Azerbaijan; Eurasia -- Economic relations; Turkey -- Foreign relations -- Azerbaijan; Public and International Affairs